PEMBELAJARAN FISIKA BERBASIS BUDAYA: INTEGRASI ANGKLUNG TERHADAP PEMAHAMAN KONSEP INTENSITAS BUNYI - Tumanggor, Awal Mulia Rejeki; Sarayar, Widyata Nikbert; Dumanaw, Varisky Abraham; Tarigan, Yustinus; Manullang, Dominikus Rojoki (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The local wisdom of Angklung as a cultural heritage is utilized in physics learning to bridge abstract concepts. This study aims to analyze the effectiveness of the Culturally Responsive Teaching (CRT) approach using Angklung in improving the conceptual understanding of sound intensity and cultural appreciation of high school students. The research method used a quasi-experimental design with a pretest-posttest nonequivalent control group model in two classes, namely experimental and control at SMA Negeri 1 Percut Sei Tuan. The experimental group used a CRT-Angklung based module that linked the physics principles of sound intensity with cultural values, and the control group used conventional learning. Results showed a significant increase in concept understanding in the experimental group (N-Gain=59,8%) compared to the control group (49,2%), with 81% of experimental students reaching the high category in cultural appreciation. Student participation observations also recorded higher enthusiasm (93%) in the experimental group during Angklung practice. These findings prove that integrating local culture through CRT not only overcomes physics misconceptions, but also strengthens students’ cultural literacy, supporting contextual learning relevant to Merdeka Belajar policy.